READING THE ELECTION FROM A SUPERVISORY PERSPECTIVE: A QUALITATIVE STUDY ON THE ROLE OF BAWASLU IN HANDLING MONEY POLITICS IN GORONTALO CITY - Zulfikar Adjie; Ramli Mahmud; Sastro M. Wantu; Rasid Yunus; Yayan Sahi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This study aims to analyze the dynamics of elections from a supervisory perspective, focusing on the role of the Election Supervisory Agency (Bawaslu) in addressing money politics practices in Gorontalo City. A descriptive qualitative approach was employed, using data collection techniques such as interviews, documentation, and direct observation of monitoring and violation-handling processes. The results show that although Gorontalo City Bawaslu operates under a strong legal foundation—namely Law Number 7 of 2017 and Government Regulation in Lieu of Law (Perpu) Number 1 of 2022—its implementation still faces numerous challenges on the ground. Out of 11 reported cases of alleged money politics, only 7 were successfully registered, while the rest could not be pursued legally. Four of these were categorized as serious violations, involving administrative, ethical, and criminal offenses. The main obstacles faced by Bawaslu include low public participation in reporting, limited access to the reporting system, insufficient supervisory capacity at lower levels, and weak law enforcement. Nevertheless, Bawaslu has taken several improvement initiatives, such as the Anti-Money Politics Village program and the use of social media for participatory supervision. The study concludes that the performance of Gorontalo City Bawaslu in handling money politics remains suboptimal and calls for comprehensive reforms in terms of resources, transparency, and strengthened collaboration with the public and law enforcement institutions to ensure clean, fair, and democratic elections.